Dementia among Senior citizens Residing at Mahalaxmi Municipality, Lalitpur - Yakha, Bhim Maya; Pokhrel, Rojan; Sah, Durga Kumari; Labh, Nisha Lal; Shakya, Shobha (Journal of Advanced Academic Research, 2026)
Background: Dementia is a progressive neurocognitive disorder marked by progressive decline in memory, thinking, behavior, and the ability to carry out daily activities. It is highly prevalent among low and middle income countries like Nepal, multiple factors are associated with prevalence of dementia. Objectives: To identify level of cognitive function and factors associated with dementia. Method: This study employed a descriptive cross-sectional design. A total of 360 participants were selected using a purposive sampling technique. Questionnaire related to Socio-demographic information, Standard valid tool community Screening Instrument of Dementia (CSID). Results: The study among 360 senior citizens of  Mahalaxmi municipality ward no. 4 revealed that slightly female were more (51.7%) with the majority belong to  age 60-70 years age group  and average age of 70.28 years.  Clinically majority of (90.0%) had at least one co-morbidity condition, with hypertension (48.6%) and diabetes (24.7%) being the most prevalent. Analysis revealed that dementia increase significantly with increasing  age (p